Recent changes of invasive meningococcal disease in France: arguments to revise the vaccination strategy in view of those of other countries - Muhamed-Kheir Taha; Joël Gaudelus; Ala-Eddine Deghmane; François Caron (Taylor & Francis Group, 2020)
In France, the incidence of invasive meningococcal disease (IMD) is around 1/100,000, with the following trends over the 2011-2018 period: a leading role of group B in subjects <15 years, a decrease of group C among <1 year since 2017, an increase of group W in all age groups including subjects <1 year since 2014 and a positive correlation between group Y and age group. In Europe, vaccination progressed with conjugate ACWY vaccines and proteins-based B vaccines. Their benefit-risk-cost balance is however not so obvious for area at low incidence (<2/100,000), explaining tremendous variations between countries, from no recommendation to recommend all available vaccines. In France, the calendar still includes only C with a good adhesion in infants but a fiasco of the catch-up campaign in adolescents and young adults. In Europe, it is time to consider not only national epidemiology but also trends in the neighborhood. The increase of group W cases encourages switching C to ACWY vaccine both in infants and adolescents. It is also time to protect infants with B vaccine. Large pedagogy on the disease is required to increase the adhesion to the vaccination and to recognize and treat earlier the residual cases.